HISTOLOGICAL CHARACTERISTICS ASH UNDER CONDITIONS OF SYMPTOMATIC GINGIVITIS IN PERIODONTITIS - Гасюк Н. В., (World of Medicine and Biology, 2014)
Results are given in the comprehensive histological studies make it possible to assert that the epithelium of attached gingival conditions for symptomatic lesions and gingivitis tsytospetsyfichnyh histofunktsionalnyh undergoes changes intercellular edema characterized by vacuolization of the cytoplasm ribbed cells. At the edge and ribbed surface of cells in the expanded mizhepitelialnyh thickets, at the expense of the integrity of desmosomes, displays segmented leukocytes. The presence of these cells is specific for chronic forms of periodontitis, and an exacerbation.
Keywords: clear; epithelium; color; white blood cells; gingivitis